2018
DOI: 10.1177/1065912918793222
|View full text |Cite
|
Sign up to set email alerts
|

Letters for Black Lives: Co-ethnic Mobilization and Support for the Black Lives Matter Movement

Abstract: Previous research demonstrates that individuals are more open to persuasion from people who share their race. However, it is not known whether this relationship holds for Asian Americans. We address this shortcoming by exploring how the race of an author influences support for, and perceptions of, the Black Lives Matter (BLM) movement. Drawing from literature on opinion formation and social identity theory, we expect that whites will be most persuaded by whites, while Asian Americans will not be particularly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…In Study 1, we found indication for increased warmth and competence ratings of both in- and outgroups under higher perceived levels of threat through COVID-19. This result might possibly be mirrored in the recent rise in support for the “Black Lives Matter” (BLM) movement by subgroups of the United States population not personally affected by systemic racism and discrimination ( Arora et al, 2020 ). Assuming that outgroup liking (instead of outgroup derogation) can lower the threat-related consequences of COVID-19, the current research might offer an explanation for the present success of the movement.…”
Section: Discussionmentioning
confidence: 99%
“…In Study 1, we found indication for increased warmth and competence ratings of both in- and outgroups under higher perceived levels of threat through COVID-19. This result might possibly be mirrored in the recent rise in support for the “Black Lives Matter” (BLM) movement by subgroups of the United States population not personally affected by systemic racism and discrimination ( Arora et al, 2020 ). Assuming that outgroup liking (instead of outgroup derogation) can lower the threat-related consequences of COVID-19, the current research might offer an explanation for the present success of the movement.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Leland Saito (1998) finds that shared interests and similar histories of discrimination led Asian Americans and Latinos in the 1980s and 1990s in Los Angeles to form interracial coalitions around issues of redistricting and anti-immigrant legislation. Maneesh Arora and Christopher Stout (2019) find that exposure to positive messages about the Black Lives Matter movement predicted greater levels of support for the movement, and more positive views of African Americans among Asian American respondents. Thus, although interracial collaboration and coalition building involves on-the-ground community organizing and relationship building, we contend that shared interests and a perception of commonality are the antecedents to greater cooperation and collaboration.…”
mentioning
confidence: 91%
“…Our analysis of the Floyd protests adds to existing literature on twentieth-century minority protest (Gillion 2012;Lee 2002;Mazumder 2018;Wasow 2020) and growing scholarship on public support for the BLM movement (Arora and Stout 2019;Bonilla and Tillery 2020;Updegrove et al 2020). Prior research has explored Americans' reactions to real (Boudreau, Mackenzie, and Simmons 2019) and hypothetical (Jefferson, Neuner, and Pasek 2020;Porter, Wood, and Cohen 2018) police killing of Black civilians; however, this work focuses on differences in attitudes caused by information provided in survey experiments and focuses on reactions to the killings themselves rather than social protest in response to killings.…”
mentioning
confidence: 99%